Development of fem model for high speed machining using small ball end milling processes - Ahmad Shahir, Jamaludin (2013)
This thesis describes the development of 2D and 3D finite element (FE) models for the high speed machining on laser sintered material, LSMEp9. The work employed finite element method (FEM) with the application of Updated Lagrangian Formulation. Mild steel, AISI1O5S was used as a comparison. Finite element simulation results of cutting force show errors of 10%, compared with experimental results when shear friction factor, m 0.8 was applied. The cutting force shows increasing values when the radial depth of cut increases for both types of materials due to chip removal rate increases. However, the cutting force decreases when the cutting speed increases due to the decreases of chip thickness and less contact time between tool and chip. The cutting temperature increases when the cutting speed increases due to increasing in 'cutting 'energy. Cutting force for laser sintered material, LSMEp9 is lower than mild steel, AISI1055 due to its lower young modulus while its cutting temperature is higher than AISI1055 due to its lower thermal conductivity. Extended studies were done for ball end mill with the diameter equal or less than 2mm. The predicted cutting temperature for ball end mills with diameter 2 mm and less shows big error compared with the experimental results due to the size effect of the ball end mill was neglected in the simulation. The heat capacity of the small size of the ball 'end mill is considerably low, thus the end mill could suffer excessive increases of cutting temperature. The large ratio of feed rate per tool radius (>0.1) could lead to increases of tool wear rate, thus worsen the heat capacity of small ball end mill. The study on effect of tool wear evolution during machining on the cutting temperature was done. In the study, cutting temperature increases when flank wear of the tool increases, while prolong machining increased the cutting temperature gradient critically. Increasing temperature during machining could affect the surface integrity of the workpiece and cutting tool, lowered the tool life and quality of the manufactured products.